Saccharomyces cerevisiae as a toxicological model to study synthetic cannabinoids and its pyrolysis products - Ferreira, C. (2015)
"Synthetic cannabinoids are among the major psychoactive drugs widespread as safe and legal alternatives to cannabis. They are commercially available as herbal incense products intended for smoke. This has led most of developed countries to concentrate efforts in order to ban the so called “legal highs”. Despite of their increasing use, there is still a lack of information on both synthetic and natural ingredients, pharmacokinetic properties and toxic effects. In fact some of the substances seem to have stronger toxicological effects when compared to their legal counterpart. Toxicological assays are paramount to know how harmful these new substances are, helping increase public awareness since several hospitalization cases have been reported due to consumption. To tackle the new challenges posed by novel drugs worldwide, we developed an approach using Saccharomyces cerevisiae as a model to investigate the toxicity of pyrolysis products of synthetic cannabinoids. S. cerevisiae."